If y = f ( x 2 + 1 2 x − 1 ) and f ′ ( x ) = sin ( x 2 ) , then find ⌊ ∣ ∣ ∣ ∣ d x d y ∣ ∣ ∣ ∣ ⌋ at x = 0 .
Notations:
Assumptions
All angles are in radians.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Shubhamkar Ayare , you don't need to provide the hint "Enter your answer of digit from 0 to 9." Can just write a complete sentence such as: "then find ..." instead of "then ... is _ ."
Log in to reply
Alright! I will follow it next time; as also correct previously written questions.
@Shubhamkar Ayare i think you have to specify if x is in degree or radian, the answer is 0 if x is in degrees
Log in to reply
Added the assumption. Thanks for pointing out!
I feel that we can assume it is in radians when it is calculus, unless it is stated otherwise.
Log in to reply
Yp, sorry about that,just learned about this now
apparently,
lim x → 0 x sin ( x ) = 1 ,only if x is in radians
if x is in degrees,
lim x → 0 x sin ( x ∘ ) = 1 8 0 π
which induces coefficients like these
d x d sin ( x ∘ ) = 1 8 0 π cos ( x ∘ )
so yeah i think there is no need to specify radians.Thanks for pointing it out- :)
Log in to reply
@Anirudh Sreekumar – Also arc length d s = r d θ , area d A = 2 1 r 2 d θ and volume.
@Anirudh Sreekumar – d x d sin ( x ∘ ) = 1 8 0 π cos ( x ∘ ) - that makes a good question! Has it been already asked?
Problem Loading...
Note Loading...
Set Loading...
y d x d y d x d y ∣ ∣ ∣ ∣ x = 0 = f ( x 2 + 1 2 x − 1 ) = d x d ( x 2 + 1 2 x − 1 ) ⋅ sin ( x 2 + 1 2 x − 1 ) 2 = ( x 2 + 1 2 − ( x 2 + 1 ) 2 ( 2 x − 1 ) ( 2 x ) ) ⋅ sin ( x 2 + 1 2 x − 1 ) 2 = ( 2 − 0 ) ⋅ sin ( − 1 ) 2 = 2 sin 1 ≈ 1 . 6 8 3
⟹ ⌊ ∣ ∣ ∣ ∣ d x d y ∣ ∣ ∣ ∣ ⌋ x = 0 = ⌊ ∣ 1 . 6 8 3 ∣ ⌋ = 1